PENGARUH LAPORAN ARUS KAS, UMUR PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Empiris Perusahaan LQ45 yang terdaftar di BEI Periode 2018-2020) - Agnes Veronica Sitanggang; Riyan Tri Ramdhani; Rizkqi Aji Gunawan; Santika Santika; Teti Ernawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The study aims to analyze the impact the company's cash flow statements, firm age, and firm size on financial performance. The population in this study is the LQ45 company listed in the BEI 2018-2020 period. The data was analyzed using the regression panel data. Research indicates that the unequaled cash flow report, firm age, and firm size have no effect on financial performance. This finding is factually contradictory to the theoretical explanation, so it cannot be used as a general reference. However, what can be explained is that there is no regression model that can be used in this study, indicating that a company's financial performance is not enough just to be seen or assessed from some data. As a result, the results of the study have not been able to reveal relevant findings. Nevertheless, this is evidence of the importance of a study to accommodate all aspects, so that the research results can explain the existing phenomena.